ANALISIS KESIAPAN LITERASI TEKNOLOGI BATTERY MANAGEMENT SYSTEM (BMS) KENDARAAN LISTRIK PADA MAHASISWA PENDIDIKAN TEKNIK MESIN - Hafid Rahmandan; Andi Maga Umara; Muhammad Yasser Arafat; Mohamad Riyandi Badu (Universitas Negeri Gorontalo, 2026)
The national energy transition demands vocational teacher candidates who are technologically literate in electric vehicle systems, including Battery Management Systems (BMS). This study aims to map the technology literacy level and pedagogical readiness of Mechanical Engineering Education students at Universitas Negeri Gorontalo regarding electric vehicle BMS technology. An exploratory descriptive quantitative design was employed with purposive sampling on sixth and eighth semester students who had completed the Automotive Electrical Systems course. Data were collected using two instruments: a BMS Cognitive Literacy Test (20 multiple choice items covering BMS functions, battery protection systems, and cell balancing) and a Pedagogical Readiness Scale measuring students' self-efficacy in teaching BMS technology at vocational high schools. Instruments were validated through expert judgment, and data were analyzed using descriptive statistics with percentage interval categories. Results show a mean cognitive test achievement of 61.5% (Fair category), with thermal management and State of Health (SoH) algorithm items recording the highest difficulty levels. The mean Pedagogical Readiness Scale reached 3.42 out of 5.00 (Fairly Ready category). A significant gap was found between students' limited technical understanding and their high pedagogical motivation and awareness. These findings imply the need to structurally integrate electric vehicle BMS content into the Automotive Electrical Systems curriculum to produce competent vocational teacher candidates relevant to the demands of the renewable energy based automotive industry.